2021
DOI: 10.1016/j.bios.2021.113309
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical biosensor for sensitive analysis of the SARS-CoV-2 RNA

Abstract: The pandemic of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) is continuously worsening globally, herein we have proposed an electrochemical biosensor for the sensitive monitoring of SARS-CoV-2 RNA. The presence of target RNA firstly triggers the catalytic hairpin assembly circuit and then initiates terminal deoxynucleotidyl transferase-mediated DNA polymerization. Consequently, a large number of long single-stranded DNA products can be produced,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 35 publications
1
62
0
Order By: Relevance
“…In such biosensors, bioreceptors are anchored on the working electrode surface to directly bind to target molecules specifically, generating changes in the interfacial properties in a concentration-dependent manner [ [18] , [19] , [20] ]. The SARS-CoV-2 has also been detected electrochemically by immunosensors [ 14 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ] and genosensors [ [33] , [34] , [35] , [36] ]. Furthermore, outstanding features of biosensors have been exploited in the detection of other viruses [ 37 , 38 ], pathogens [ 39 ], other infections [ 18 ], cancer biomarkers [ [40] , [41] , [42] ] and other diseases-related biomarkers [ 43 ] demonstrating to be promising analytical tools that can help to solve current diagnosis limitations [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In such biosensors, bioreceptors are anchored on the working electrode surface to directly bind to target molecules specifically, generating changes in the interfacial properties in a concentration-dependent manner [ [18] , [19] , [20] ]. The SARS-CoV-2 has also been detected electrochemically by immunosensors [ 14 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ] and genosensors [ [33] , [34] , [35] , [36] ]. Furthermore, outstanding features of biosensors have been exploited in the detection of other viruses [ 37 , 38 ], pathogens [ 39 ], other infections [ 18 ], cancer biomarkers [ [40] , [41] , [42] ] and other diseases-related biomarkers [ 43 ] demonstrating to be promising analytical tools that can help to solve current diagnosis limitations [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Peng et al have proposed a SARS-CoV-2 detection method that uses a catalytic assembly circuit and DNA polymerization in the presence of targeted RNA [82] . The biorecognition elements used were hairpin structures and were immobilized on the surface for specificity.…”
Section: Biosensors For the Detection Of Pathogensmentioning
confidence: 99%
“…The biorecognition elements used were hairpin structures and were immobilized on the surface for specificity. The sensor has shown its capability in SARS-CoV-2 RNA detection at concentrations as low as 2.6 × 10 −6 nM, along with linear responses in concentration ranges between 10 −5 and 1 nM [82] . In a similar study targeting SARS-CoV-2 RNA, Zhao et al reported the development of a biosensor that does not require any pretreatment steps, such as nucleic acid amplification and reverse transcription, which conventional methods often require [76] .…”
Section: Biosensors For the Detection Of Pathogensmentioning
confidence: 99%
“…Among the wide variety of transduction mechanisms for detecting nucleic acid amplification, one can find electrochemical-based sensors [27] , [28] , optical devices [29] , colorimetric assays [30] , luminescence-based sensors [31] , and surface plasmon resonance apparatus [32] , to mention only a few. Particularly, electrochemical transduction has demonstrated its ability to provide a cost-effective alternative to circumvent manufacturing and integration processes to robust devices.…”
Section: Introductionmentioning
confidence: 99%